Applying Innovative Learning Media To Improve Numerical Literacy In Primary School - Anugrah, Rifki; Yulandhini, Yolla; Kulsum, Siti; Aldinosa, Yogi; Arifin, M. Zainal (International Conference on Elementary Education, 2025)
Improving numerical literacy in elementary schools is a major concern in the world of education in Indonesia. Several studies have emphasized the importance of using innovative and creative learning media to improve students' understanding of mathematical concepts and mathematical skills. This article examines the application of innovative learning media to improve numerical literacy in elementary schools. The method used in this study is a literature review based on articles obtained from Google Scholar and Garuda searches, with a total of 30 relevant articles over an 8-year period, namely from 2018 to 2025. The research process was carried out by identifying, studying and synthesizing research results that discuss innovative strategies in the field of numerical learning. The results of the analysis show that the use of technology-based media, educational games and interactive methods can consistently improve students' learning motivation and numerical skills. These findings emphasize the need for further development of innovative learning media to improve students' numerical literacy at the elementary level, as well as a review for references as a means to improve learning resources. This study recommends a new path in the form of using digital media as a form of innovative learning media to improve elementary school students' numerical literacy